2007
DOI: 10.1143/jjap.46.6601
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystal Alignment Effects for Nematic Liquid Crystal on Homeotropic Polyimide Surface Using New Ion-Beam Source

Abstract: We have studied the liquid crystal (LC) alignment and tilt angle generation of a nematic liquid crystal (NLC) on a homeotropic polyimide (PI) surface using a new ion beam source. The tilt angle of the NLC on the homeotropic PI surface for all incident angles is about 38 and this angle has a stabilization trend. A good LC alignment of the NLC on the homeotropic PI surface by to exposure ion beam of 45 incidence angle was observed. Also, the tilt angle of the NLC on the homeotropic PI surface by to exposure ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…For instance, the vertical alignment of LC molecules, wherein the direction of the LC molecules is oriented vertically relative to the surface, has been investigated for optical sensor applications owing to susceptibility to small perturbations [ 21 , 22 , 23 , 24 ]. It has been found that LC molecules could be oriented by the anisotropic properties of a surface via contact and non-contact methods, such as rubbing, lithography, stretching, polarized ultraviolet irradiation, and ion beam treatment [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Among these, the rubbing technique is the conventional contact method used to align LC molecules because of its simplicity and rapidity [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the vertical alignment of LC molecules, wherein the direction of the LC molecules is oriented vertically relative to the surface, has been investigated for optical sensor applications owing to susceptibility to small perturbations [ 21 , 22 , 23 , 24 ]. It has been found that LC molecules could be oriented by the anisotropic properties of a surface via contact and non-contact methods, such as rubbing, lithography, stretching, polarized ultraviolet irradiation, and ion beam treatment [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Among these, the rubbing technique is the conventional contact method used to align LC molecules because of its simplicity and rapidity [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the vertical orientation of nematic LCs, wherein the director of the nematic LCs is oriented vertically to the surface of the substrate, has been studied for sensor applications because of its susceptibility to small perturbations and binding events [ 15 , 16 , 17 , 18 ], which can be observed by an optical apparatus such as a polarized optical microscopy (POM) [ 19 , 20 ]. It has been demonstrated that LC molecules can be aligned by the anisotropic characteristics of a surface via numerous contact and noncontact methods, such as mechanical rubbing, stretching, lithography, polarized ultraviolet (UV) radiation, and ion beam treatment [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Among these, the mechanical rubbing of polymeric surfaces is the most commonly used contact method to obtain a uniform orientation of LC molecules because of its simplicity and rapidity [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most well-known example of these efforts is the development of the liquid crystal display (LCD), which involves an orientation layer, and is widely used in portable display devices such as smartphones [ 10 , 11 ]. It has been found that liquid crystal (LC) molecules can be oriented by the anisotropic characteristics of a substrate surface via numerous contact and noncontact methods, such as mechanical rubbing, stretching, lithography, polarized ultraviolet (UV) radiation, and ion beam treatment [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Due to its simplicity and rapidity, the mechanical rubbing of polymeric surfaces is the most commonly used contact method for controlling not only the orientation direction, but also the pretilt angle of the LC molecules [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%